2012
DOI: 10.1111/j.1834-7819.2012.01677.x
|View full text |Cite
|
Sign up to set email alerts
|

Enamel roughness and depth profile after phosphoric acid etching of healthy and fluorotic enamel

Abstract: Background: Dental fluorosis requires aesthetic treatment to improve appearance and etching of enamel surfaces with phosphoric acid is a key step for adhesive restorations. The aim of this study was to evaluate surface roughness and a depth profile in healthy and fluorotic enamel before and after phosphoric acid etching at 15, 30 and 60 seconds. Methods: One hundred and sixty enamel samples from third molars with no fluorosis to severe fluorosis were evaluated by atomic force microscopy. Results: Healthy ename… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 15 publications
4
23
0
4
Order By: Relevance
“…21 With respect to the micrographs taken from molars with SEF, after etching for 15 seconds, the surface appeared almost intact; when performing etching for 150 seconds, a rough surface was observed, but the SBS was less than that obtained with etching for 15 seconds. This was explained by Torres-Gallegos et al, 22 who used AFM to evaluate the surface roughness and depth profile in healthy and fluorosed enamel. They concluded that increasing the etching time in SEF cases can decrease the surface roughness and depth profile, which may produce a less effective micromechanical enamel surface for effective adhesive bonding.…”
Section: Discussionmentioning
confidence: 99%
“…21 With respect to the micrographs taken from molars with SEF, after etching for 15 seconds, the surface appeared almost intact; when performing etching for 150 seconds, a rough surface was observed, but the SBS was less than that obtained with etching for 15 seconds. This was explained by Torres-Gallegos et al, 22 who used AFM to evaluate the surface roughness and depth profile in healthy and fluorosed enamel. They concluded that increasing the etching time in SEF cases can decrease the surface roughness and depth profile, which may produce a less effective micromechanical enamel surface for effective adhesive bonding.…”
Section: Discussionmentioning
confidence: 99%
“…In this study design, fluoride-release was monitored in the presence of an enamel substrate that underwent pre-treatment with acid etching prior to sealant application. Etching sound enamel with 37% phosphoric acid for 15 s removes approximately 3 µm of enamel tissue, exposes the enamel prisms, and affects demineralization up to a depth of 50 µm 32,33) . In TF, 40% phosphoric acid was used and, therefore, the enamel surface was probably demineralized more or less to a similar extent.…”
Section: Discussionmentioning
confidence: 99%
“…Nesta abordagem, busca-se a criação de espaços no substrato dental, seguida pela penetração e pela polimerização da resina adesiva. O condicionamento ácido do esmalte causa a dissolução da periferia ou do centro do prisma de esmalte, criando porosidades e aumentando a energia de superfície desse substrato 3,4 . Essas alterações possibilitam a penetração do adesivo nas porosidades do esmalte, formando a zona de interdifusão, responsável pela união 1,2,5 .…”
Section: Introductionunclassified